Optimal Web Surfing And Congestion Control For Internet Routing - S.R., Sudharsanan (2000)
The objective of this research can be categorised into the following aspects : (a) To present an extensive analysis on Internet Routing - Methods, Protocols, Internals, Issues and Trends. (b) To develop an efficient minimal cut set algorithm in order to extract the minimal paths between any source and destination links in a web link network and use this approach for graphical design of web link structures. To explore optimal web surfing by improvising the classical routing algorithms using fuzzy distance measurers. (d) To present a comprehensive survey of Internet multimedia protocols such as RTP, RTCP, RTSP and TFRCP, and to analyse the performances of SIP and H.323 for signaling and control of Internet telephony, RSVP and YESSIR for resource reservation in the Internet. (e) To analyse the problems of video streaming over the Internet and to develop qualitative solution models with regard to video streaming based on two architectures ( RTP/RTCP and TCP/UDP/IP) and (f) To attain global optimisation through end-to-end congestion control for Internet Routing and to develop a modified congestion control algorithm for routers in the Internet. In order to study and analyse the internal organisation of links in a web site, a recursive algorithm is used to extract all the links in a specific web-site and link connectivity is represented as a tree structure using graphs and logic gates. Minimal cut sets are extracted to minimise the number of clicks while surfing from the source page to the destination page, that is, to find the minimal path between them. Identifying the presence of minimal cut sets in a web link network positively enhances the reliability and security of the web site. An efficient minimal cut set algorithm is developed to extract the minimal paths between any source and destination links in a web link network. The proposed algorithm is tested on a link tree and the minimal cut sets are obtained. And this approach is found to be effective for the reliability and security of a web site. To explore optimal web surfing ( shortest path routing), fuzzy simulation of routing algorithms for finding the optimal path set of links to a target web site in a web link network is implemented. Fuzzy distance measures are derived from the subjective estimation of each link in a web link network by different users with regard to the retrieval rate. Classical routing algorithms (Floyd-Warshall's, Dijkstra's and Bellman-Ford's) are extended using fuzzy hamming distance to explore optimal web surfing. Fuzzy Hurwicz rule is taken into account in establishing the optimistic and pessimistic view of different users for various path sets in the web link network. An optimal surfing path is estimated in a web link network using the implemented fuzzy distance based routing algorithms. A range of protocols are certainly necessary to provide streaming multimedia across the Internet. These protocols include mechanisms for data transfer (RTP), resource reservation (RSVP), session setup for specific applications ( SDP, SAP), media-on-demand, control of stored and live multimedia (RTSP), Internet telephony, multimedia conference session initiation, call control (SIP), quality-of-service monitoring (RTCP) and congestion control for time-sensitive multimedia data streams (TFRCP). An extensive survey of Real-time Transport Protocol (RTP), Real-time Transport Control Protocol (RTCP), Real-Time Streaming Protocol ( RTSP) and TCP-friendly Rate Control Protocol ( TFRCP) are presented. The performances of the Session Initiation Protocol (SIP) and H.323 standards for signaling and control for internet telephony, Resource ReSerVation Protocol ( RSVP) and Yet another Sender Session Internet Reservations ( YESSIR) for resource reservation in the Internet have been analysed and compared. Based on the performances of the above protocols, certain improvements are suggested for efficient transfer of real-time continuous media data. The problems of video streaming over the Internet I.e., transferring a video file over an Internetwork effectively without the loss of video data is studied and analysed. Video Streaming architectures based on RTP/RTCP and TCP/UDP/IP are analysed and comparisons have been made about real time video streaming applications. Possible qualitative solutions for the improvement of Video Streaming over an Internet. Environment is developed based on key components such as multicast capability , real time data transport, assured QoS, retransmission, forward error correction, receiver buffering and adaptation. In order to address the steady rise of packet loss rates in real time media streaming, two important destination based congestion control algorithms in packet switched networks are examined. They are Random Early detection (RED) algorithm and modified approach called Derivative Random Drop (DRD) algorithm. The original RED algorithm presents two variants of RED namely RED_VAR-1 and RED-VAR-2. A new proposal has been made for the RED algorithm with two more different variants called as RED-VAR-3 and RED-VAR-4. The performances and the result of all RED variants have been presented. A modified congestion control algorithm ( RED-VAR-4 algorithm) for real time media streaming applications over an Internet routing environment is proposed.